Successful treatment of plantar warts with intralesional bleomycin and electroporation: pilot prospective study - Paola Pasquali; Azael Freites-Martinez; Salvador Gonzalez; Enrico P. Spugnini; Alfonso Baldi (Mattioli1885, 2017)
Background: Numerous studies have been performed to evaluate the efficacy of intralesional bleomycin for the treatment of warts with inconsistent result. Nevertheless, it is well known that the cytotoxicity of bleomycin can be enhanced in vivo by 300 to 700-fold by electroporation. Objective and Methods: In this article, we present an interventional, one-center, prospective case series, clinical trial of the effectiveness of intralesional bleomycin combined with electroporation for the treatment of plantar warts, in comparison to the use of intralesional bleomycin alone. Results: The study's cohort included 12 men and 10 women, with a mean age of 53.8 years. A total of 22 warts were treated. In dividing the patients in two groups (complete remission against all the others) and analyzing the different outcomes in the two arms of patients, a statistical significant difference was found (p=0.0015), proving a greater efficacy of the treatment with bleomycin combined with ECT as opposed to bleomycin alone. Electroporation was always well tolerated by the patients with no discomfort. Conclusions: This study serves as a basis for the application of novel protocols in the treatment of different benign and locally malignant skin lesion by means of electroporation.